Unveiling the Impact of National Task Force to End Local Communist Armed Conflict (NTF-ELCAC) in Four Barangays of Tangub City - Casuyon, Reyscielle; Embornas, Amabelle (Journal of Interdisciplinary Perspectives, 2024)
The Communist armed conflicts in the Philippines trace their origins to various communist organizations dating back to 1930, notably the Hukbalahap Rebellion (1942–1954) led by the Communist Party of the Philippines (CPP). Subsequently, the New People’s Army (NPA), an offshoot of the CPP, emerged in 1969, continuing the rebellion. In response, the Local Government Unit of Tangub, alongside agencies like the Department of Interior and Local Government (DILG), Department of Social Welfare and Development (DSWD), the Armed Forces of the Philippines (AFP), and Philippine National Police (PNP), adopted the National Task Force to End Local Communist Armed Conflict (NTF-ELCAC) under President Rodrigo Roa Duterte's EO 2018, aiming to achieve peace and halt conflicts between the NPA and AFP in affected barangays. This study assessed the implementation of NTF-ELCAC in Tangub City, Misamis Occidental, using a mixed-method approach involving both qualitative and quantitative methods. Surveys were conducted with 140 respondents from four conflict-affected barangays: Sicot, Owayan, San Antonio, and Hoyohoy. Findings revealed that respondents were well-informed about communist groups in the Philippines and NTF-ELCAC, expressing positive feedback on project experiences, improved socio-economic conditions, enhanced peace and order, and strengthened relationships with the government. Suggestions for program improvement and policy issues were also highlighted. Theoretical implications underscored the importance of social solidarity and the role of social institutions in fostering a balanced society.